A prospective birth cohort study on cord blood folate subtypes and risk of autism spectrum disorder. Issue 5 (25th August 2020) - Raghavan, Ramkripa; Selhub, Jacob; Paul, Ligi; Ji, Yuelong; Wang, Guoying; Hong, Xiumei; Zuckerman, Barry; Fallin, M Daniele; Wang, Xiaobin
ABSTRACT: Background: We previously reported that extremely high concentrations of maternal plasma folate were associated with increased risk of autism spectrum disorder (ASD) in children. This study explored whether specific types of folate in cord blood have differential association with ASD. Objectives: In the Boston Birth Cohort (BBC), we assessed the association between cord blood unmetabolized folic acid (UMFA), 5-methyl tetrahydrofolate (THF), and total folate and a child's ASD risk. In a subset, we explored whether the association between UMFA and ASD risk can be affected by the dihydrofolate reductase ( DHFR ) genotype and cord plasma creatinine. We also examined prenatal correlates of cord UMFA concentrations. Methods: This report included 567 BBC children (92 ASD, 475 neurotypical), who were recruited at birth and prospectively followed at the Boston Medical Center. ASD was defined from International Classification of Diseases (ICD)-9 and ICD-10 codes documented in electronic medical records. Results: Children with cord UMFA in the highest, versus lowest quartile, had a greater ASD risk (adjusted OR, aORquartile4 : 2.26; 95% CI: 1.08, 4.75). When stratified by race/ethnicity, the association was limited to 311 (45 ASD) Black children (aORquartile4 : 9.85; 95% CI: 2.53, 38.31); a test of interaction between race/ethnicity and cord UMFA concentrations was significant ( P  = 0.007). The UMFA-ASD association in Black children slightly attenuated after adjusting for cord plasma creatinine ( P  = 0.05). There was no significant association between cord 5-methyl THF, total folate, DHFR genotype, and ASD risk. Cord total folate and maternal supplement intake during second trimester were associated with higher cord UMFA. Conclusions: Higher concentrations of cord UMFA, but not 5-methyl THF or total folate, were associated with a greater risk of ASD in Black children. This study in a preterm-birth-enriched cohort raises more questions than it could answer and underscores the need for additional investigations on the sources and role of cord UMFA in children's neurodevelopmental outcomes and underlying mechanisms.